On Monitoring Position of a Charged Particle Moving near a Metal Sphere by Means of Diffraction Radiation - Syshchenko, V. V.; Tarnovsky, A. I. (Surface investigation, x-ray, synchrotron and neutron techniques, 2023)
— A uniformly moving charged particle generates transition radiation when moving in an inhomogeneous medium (in particular, when crossing the interface between two media) and diffraction radiation when moving near medium inhomogeneities without crossing their boundaries. Both diffraction and transition radiation can be used to detect particles and monitor beams in accelerators. While methods based on the transition radiation of particles for diagnostics of both relativistic and nonrelativistic beams are widespread, the application of diffraction radiation for these goals remains the subject of research. Diffraction-radiation generation weakly perturbs the motion of a particle beam, which makes it possible to develop nondestructive beam-diagnostics methods. The description of the diffraction radiation of a nonrelativistic charged particle for a conducting sphere was constructed earlier by means of the image method known from electrostatics. The method for finding the parameters of particle flight by the sphere was proposed within the framework of this approach; it used a single point detector recording the intensity and polarization of diffraction radiation. Here we propose a scheme with three detectors that solves the same problem without recording the radiation polarization.